Estudios taxonomics y ecogeograficos de las cucurbitaceae latinoamericanas de importancia economica - Lira-Saade, Rafael (1996)
Published in collaboration with Instituto de Biologia, UNAM, Mexico. As a preamble for future conservation actions for the cucurbitaceae in Latin America, IPGRI commissioned a taxonomic and ecogeographic study of the different genepools of cucurbits, squashes, gourds, chayotes and achokchas, involving the revision of 2300 herbarium specimens, the collation of 3400 bibliographic references, and field work in Mexico, Guatemala and Costa Rica.